Meta-Analysis: The Association between Social Support and Postpartum Depression - Ardiani, Ardiani; Soemanto, RB.; Murti, Bhisma (Journal of Maternal and Child Health, 2020)
Background: Postpartum depression is a mood disorder that occurs in the first year after childbirth, which affects mothers, babies and their families. The prevalence of post